The Implementation of ZIP Regression and ZINB Regression to Overcome Overdispersion of Death Cases Due to Filariasis in Indonesia - Azizah; Dewi Novita Sari (Universitas PGRI Palembang, 2023)
Filariasis occurs as a result of parasitic infection by a mosquito vector. Filariasis affects the lymph and causes blood loss in the body. Filariasis is uncured. Therefore, prevention measures are needed to reduce the number of deaths. Filariasis generally does not cause death directly and rarely occurs. However, this results in an excess number of zeros in the data, which causes overdispersion. The data used were obtained from the book Indonesia Health Profile 2021, which covers the research area of Indonesia. The ZIP and ZINB regression methods were used to model the factors that affect mortality due to filariasis. Based on research conducted using ZINB regression, the results showed that the percentage of households with good sanitation has a significant effect on deaths caused by filariasis.